2015
DOI: 10.1111/aji.12374
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Shock Proteins 70 Induce Pro‐Inflammatory Maturation Program in Decidual CD1a+ Dendritic Cells

Abstract: HSP70 binds CD91 and TLR4 on decidual CD1a(+) DCs, causes their maturation, and increases IL-15 in the context of Th1 cytokine/chemokine domination, which could support immune response harmful for ongoing pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…23 Sections were deparaffinized, hydrated, and washed, antigens were retrieved, and nonspecific antibody binding was prevented at RT, as described above for the immunohistological method. 23 Sections were deparaffinized, hydrated, and washed, antigens were retrieved, and nonspecific antibody binding was prevented at RT, as described above for the immunohistological method.…”
Section: Immunofluorescence Of Paraffin-embedded Tissue Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Sections were deparaffinized, hydrated, and washed, antigens were retrieved, and nonspecific antibody binding was prevented at RT, as described above for the immunohistological method. 23 Sections were deparaffinized, hydrated, and washed, antigens were retrieved, and nonspecific antibody binding was prevented at RT, as described above for the immunohistological method.…”
Section: Immunofluorescence Of Paraffin-embedded Tissue Sectionsmentioning
confidence: 99%
“…Immunofluorescence was performed on paraffin-embedded early pregnancy decidual sections (6 μm) from normal and pathological pregnancies (BO and MA), according to the protocol described earlier. 23 Sections were deparaffinized, hydrated, and washed, antigens were retrieved, and nonspecific antibody binding was prevented at RT, as described above for the immunohistological method. Tissue sections were subsequently incubated overnight at +4°C with anticytokeratin/anti-GNLY, anticytokeratin/anti-Apaf-1-cytokeratin/ anti-NF-κB, anti-GNLY/anti-Apaf-1, anti-CD56/anti-Apaf-1, and anti-CD56/anti-GNLY antibodies.…”
Section: Immunofluorescence Of Paraffin-embedded Tissue Sectionsmentioning
confidence: 99%
“…The immunohistological labeling was quantified using the Alphelys Spot Browser 2 integrated system (Alphelys, Plaisir, France), according to our previous publications. 5,21 The software detected objects of interest on the basis of pixel color properties (wavelength, intensity, and saturation), grouping, and morphological attributes such as size and shape. The algorithms were designed to determine the count of …”
Section: Immunohistologymentioning
confidence: 99%
“…5,21,22 Briefly, decidual tissue samples from normal and pathological pregnancies were exposed to collagenase digestion and resulting decidual cell suspension centrifuged on gradient den- Decidual adherent cells, that flattened to the bottom of the Petri dish, were composed mostly of stromal cells, macrophages, some glandular, endothelial, extravillous trophoblast, 22 and immature dendritic cells. 23 All of these adherent cell types were excluded in our experimental DLs, which were collected by pipette as non-adherent cell fraction of DMCs.…”
Section: Isolation Of Decidual Mononuclear Cells and Decidual Lymphmentioning
confidence: 99%
“…Hsp72 could be secreted and the extracellular Hsp72 acted as a danger signal [7] to alarm surrounding cells and induced TLR2/4 mediated inflammation through Siglec receptors [8]. It was also found that Hsp72 could stimulate dendritic cell maturation [9,10] so as to elevate the antigen presenting capability. IFNγ secreted by the effector cells, predominantly by Th cells [11], could stimulate cancer cells to release Hsp72 [12].…”
mentioning
confidence: 99%